Droplet digital PCR as a novel detection method for quantifying microRNAs in acute myocardial infarction. (15th April 2018) - Robinson, S.; Follo, M.; Haenel, D.; Mauler, M.; Stallmann, D.; Tewari, M.; Duerschmied, D.; Peter, K.; Bode, C.; Ahrens, I.; Hortmann, M.
Abstract: Background: micro-RNAs have shown promise as potential biomarkers for acute myocardial infarction and ischemia-reperfusion injury (I/R). Most recently droplet digital polymerase chain reaction (ddPCR) has been introduced as a more reliable and reproducible method for detecting micro-RNAs. Aims: We aimed to demonstrate the improved technical performance and diagnostic potential of ddPCR by measuring micro-RNAs in ST-elevation myocardial infarction (STEMI). Methods: A dilution series was performed in duplicate on synthetic Caenorrhabditis elegans -miR-39, comparing quantitative real-time PCR (qRT-PCR) and ddPCR. We used ddPCR and qRT-PCR to quantify the serum levels of miR-21, miR-208a and miR-499 between STEMI patients ( n = 24) and stable coronary artery disease (CAD) patients ( n = 20). In STEMI, I/R injury was assessed via measurement of ST-segment resolution. Results: In the dilution series, ddPCR demonstrated superior coefficient of variation (12.1%vs.32.9%) and limit of detection (0.9325 vs.2.425copies/μl). In the patient cohort, ddPCR demonstrated greater differences in miR-21 levels (2190.5 vs. 484.7 copies/μl; p = 0.0004 for ddPCR and 136.4 vs. 122.8 copies/μl; p = 0.2273 for qRT-PCR) and in miR-208a (0 vs. 24.1 copies/μl, p = 0.0013 for ddPCR and 0 vs. 0 copies/μl, p = 0.0032 for qRT-PCR), with similar differences observed in miR-499 levels (9.4 vs. 81.5 copies/μl, p < 0.0001 for ddPCR and 0 vs. 19.41 copies/μl, p < 0.0001 for qRT-PCR). ddPCR also more accurately defined STEMI for all miRNAs (area under the curve (AUC) of 0.8021/0.7740/0.9063 for miR-21/208a/499 with ddPCR vs. AUC of 0.6083/0.6917/0.8417 with qRT-PCR). However, there was no association between miR-21/208a/499 levels and ischemia-reperfusion injury. Conclusion: ddPCR demonstrates superiority in both technical performance and diagnostic potential compared to qRT-PCR. Ultimately, this supports its use as a diagnostic method for quantifying micro-RNAs, particularly in large multi-center trials.